Girls’ Education : The Role of Educational Policies in Mauritania and Guinea - Maiga-Toure, Aminata (World Bank, Washington, DC, 2012)
This article analyzes the role of educational policies as a success factor for girls' education and focuses in two countries, Mauritania and Guinea, that have successfully addressed this issue. It also briefly mentions the current situation in Burkina Faso and Mali. The key objective of this research effort was to understand and explain the practices that help girl students to succeed in school, and the underlying circumstances. The research revealed that the problems and successes of girls' schooling are part of a whole dynamic, in which socio-cultural, school and institutional factors overlap and interact.